(untitled) (Моделювання, керування та інформаційні технології, 2023)
Unemployment is one of the most important problems in the world. It hinders the socio-economic development of the country, hinders the improvement of the standard of living of the population. In the economic literature, special attention is paid to the analysis of the economic and social consequences of unemployment. Unemployment gives rise to several problems of particular acuteness. Among them is the problem of social inequality